2015
DOI: 10.1121/1.4901713
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the niche effect for single flat panels with or without attached sound absorbing materials

Abstract: The sound transmission loss (STL) of a test sample measured in sound transmission facilities is affected by the opening in which it is located. This is called the niche effect. This paper uses a modal approach to study the STL of a rectangular plate with or without an attached porous material located inside a box-shaped niche. The porous material is modeled as a limp equivalent fluid. The proposed model is validated by comparison with finite element/boundary element computations. Using a condensation of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some decades ago, several experimental studies demonstrated the niche effect [5][6][7][8][9], which was later investigated in theoretical and numerical studies [10][11][12][13]. So far, the following general findings on the niche effect have been obtained: 1) the effect is significant below the critical coincidence frequency; 2) the effect depends on the position of the specimen in the niche; 3) the lowest STL is obtained when the sample is located in the middle of the niche; 4) the highest STL is obtained when the sample is mounted flush at one of the edges of the niche; 5) the effect depends on the sectional shape of the niche around the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Some decades ago, several experimental studies demonstrated the niche effect [5][6][7][8][9], which was later investigated in theoretical and numerical studies [10][11][12][13]. So far, the following general findings on the niche effect have been obtained: 1) the effect is significant below the critical coincidence frequency; 2) the effect depends on the position of the specimen in the niche; 3) the lowest STL is obtained when the sample is located in the middle of the niche; 4) the highest STL is obtained when the sample is mounted flush at one of the edges of the niche; 5) the effect depends on the sectional shape of the niche around the specimen.…”
Section: Introductionmentioning
confidence: 99%